Optimalisasi Eksekusi Restitusi Bagi Anak yang Menjadi Korban Tindak Pidana Kekerasan Seksual Dalam Mewujudkan Kepastian Hukum - Ricardo, David; -, Ismail; Iryani, Dewi (jurnal.unprimdn.ac.id, 2024)
This research aims to analyze the implementation of restitution execution for child victims of sexual violence in Indonesia, as well as identify obstacles in its implementation that result in a lack of legal certainty in the provision of restitution. The aim is to improve the effectiveness and fairness of the process, especially in ensuring that child victims of sexual violence receive restitution by the court's decision. The research method used is normative juridical, using secondary data sources as primary, secondary, and tertiary legal materials. The results found that although there have been progressive legal changes to protect children from crime, such as restitution, its implementation is still faced with several obstacles, including a lack of clarity in law enforcement if the perpetrator cannot pay restitution. As a result, child victims of sexual violence often do not receive court-mandated restitution due to the lack of appropriate sanctions against perpetrators who fail to fulfill restitution obligations.